1988
DOI: 10.1111/j.1469-8137.1988.tb03727.x
|View full text |Cite
|
Sign up to set email alerts
|

The germination characteristics of seeds from Lychnis viscaria L. (Viscaria vulgaris Bernh.), Potentilla rupestris L. and Veronica spicata L.

Abstract: S U M M A R YThe ettects of temperature, date of sowing and the presence or absence ol light on the percentage germmation by seeds of Lvchitii visitirin L. {Viscaria vid^aris Bernh.), Potetitil/a rtipestris L. and Veronica spicata L. were studied. It was found that both in controlled environments and in the open, the order of time-to-germination was the same, nameK-L. z-israiia, V. spiiata and finally, P. rupestris. The latter species reqinred a temperature in e.vcess of 10 °C to germinate and V. spicata requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…Veronica seeds need light for germination (Whittington et al 1988), which explains the low emergence in thick moss. In contrast to the emergence of Arenaria, seedling emergence of Veronica was slightly higher in thin moss than on bare soil (Fig.…”
Section: Effect Of Bryophyte Cover On Seedling Emergencementioning
confidence: 99%
“…Veronica seeds need light for germination (Whittington et al 1988), which explains the low emergence in thick moss. In contrast to the emergence of Arenaria, seedling emergence of Veronica was slightly higher in thin moss than on bare soil (Fig.…”
Section: Effect Of Bryophyte Cover On Seedling Emergencementioning
confidence: 99%
“…This suggests a general disadvantage of small‐seeded species, not directly related to shading (Jakobsson & Eriksson, ), but with complete lack of germination, it is likely that these species’ require more suitable conditions for their germination (see Appendix ). For example, Lychnis viscaria often requires bare soil for germination success (Whittington, Wilson, & Humphries, ) (which we did not provide in order to mimic natural field conditions as much as possible) and Hypericum perforatum shows large variation in germination success depending on site properties (Pérez‐García et al., ). Hence, the simulated natural conditions in the seed sowing experiment limit the interpretation of our results, but also exemplify one challenge with field experiments, and a reason why they may not provide similar results as greenhouse experiments (cf.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a general disadvantage of small-seeded species, not directly related to shading (Jakobsson & Eriksson, 2000), but with complete lack of germination, it is likely that these species' require more suitable conditions for their germination (see Appendix S2). For example, Lychnis viscaria often requires bare soil for germination success (Whittington, Wilson, & Humphries, 1988) (which we did not provide in order to mimic natural field conditions as much as possible) and…”
Section: Seed Sowing Experimentsmentioning
confidence: 99%
“…Whittington et al . (1988), in agreement with the results of Pring (1958), found that when unimbibed seeds were buried (5 mm), only 3% emergence had occurred after 16 days, which is a similar result to that recorded for dark‐grown seeds in Petri dishes.…”
Section: Floral and Seed Charactersmentioning
confidence: 99%